A new method using 1, 3, 5-triazine as an umpolung hydrogen cyanide equivalent toward the syntheses of isoquinolinone and 2-pyridone derivatives. Issue 43 (24th October 2018) - Hayashida, Joji; Yoshida, Shinya
Graphical abstract: Highlights: An efficient and simple approach to access various isoquinolinone and 2-pyridones derivatives. A useful application of 1, 3, 5-trizaine as an umpolung hydrogen cyanide synthetic equivalent. A novel cyclization for the synthesis of amino-isoquinoline derivatives. Abstract: An investigation of Hermecz and Hartenstein's cyclization methods was conducted. Overcoming the limited substrate scope allowed the expansion of the synthetic application of 1, 3, 5-triazine as an umpolung hydrogen cyanide equivalent. The reaction proceeded under mild conditions to provide various isoquinolinone and 2-pyridone derivatives with excellent yields.